2021
DOI: 10.3389/fpsyg.2021.743306
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Coronavirus Disease 2019 Pandemic on Investor Sentiment—Evidence From A-Share Listed Companies in China

Abstract: In a DID model, this study examines the impact of the coronavirus disease 2019 (COVID-19) pandemic on the investor sentiment in the financial market of China using monthly panel data on newly listed Chinese companies between October 2019 and June 2020. The outbreak of the pandemic is shown to exert a significant negative impact on investor sentiment. A future industry heterogeneity analysis shows that the pandemic has driven up investor sentiment in the pharmaceutical sector while having a significantly negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…US investors' technical analysis valuation investment decision-making during the COVID-19 pandemic era was mostly based on unintentional errors in their worldview and calculated guesses related to prior knowledge. The findings of this study contradicted the studies done in China by Song et al (2021) and Jan et al (2022) that showed that the pandemic outbreak hurt investors' confidence in investment decision-making. The US investors were better positioned based on their experience and market information availability.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…US investors' technical analysis valuation investment decision-making during the COVID-19 pandemic era was mostly based on unintentional errors in their worldview and calculated guesses related to prior knowledge. The findings of this study contradicted the studies done in China by Song et al (2021) and Jan et al (2022) that showed that the pandemic outbreak hurt investors' confidence in investment decision-making. The US investors were better positioned based on their experience and market information availability.…”
Section: Resultscontrasting
confidence: 99%
“…A study by Song, Hao, and Lu (2021) explored the influence of the COVID-19 pandemic on investor emotion in China's financial market between October 2019 and June 2020. The pandemic outbreak hurt investor sentiment.…”
Section: The Covid-19 Pandemic Does Not Mediate the Relationship Betw...mentioning
confidence: 99%
“…In addition to financial markets, Baker & Wurgler (2007) were the first to explore investor sentiment from a macroeconomic perspective, emphasizing its exogenous origins and empirical effects [21]. For example, the impact of energy prices on investor sentiment in the United States [22] (Apergis et al, 2017) and the importance of investor sentiment in key events such as the COVID-19 pandemic, revealing its impact on investor behavior and market dynamics [23] (Song et al, 2021). In addition, it was found that investor sentiment affects trade to varying degrees under different market conditions, influencing returns and volatility [24] (Liu & An, 2018).…”
Section: Research On the Impact Of Investor Sentimentmentioning
confidence: 99%
“…This expectation is due to investors' anticipation of the increasing demand for pharmaceutical products. The rising trend in pharmaceutical stock price is witnessed during COVID-19 pandemic (Song et al, 2021). However, COVID-19 related news and economic related announcements do not cause irrational investment in the pharmaceutical or healthcare stocks (Sun et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%